In Vitro Investigation of Auranofin as a Treatment for Clostridium difficile Infection - Christine Roder; Eugene Athan (Adis, Springer Healthcare, 2020)
Abstract Background Clostridium difficile infection is the leading cause of hospital-acquired gastrointestinal infection and incidence rates continue to rise. Clostridium difficile infection is becoming increasingly complex to treat owing to the rise in treatment failures and recurrent infections. There is a clear need for new therapeutic options for the management of this disease. Objective This study aimed to assess auranofin, a drug approved for the treatment of arthritis, as a treatment for C. difficile infection. Previous investigations have demonstrated potential antimicrobial activity of auranofin against C. difficile and other organisms. Methods The activity of auranofin was assessed by in vitro investigations of its effect on C. difficile M7404 growth, vegetative cell viability, and spore viability. Activity of auranofin was also compared to that of the current treatments, metronidazole and vancomycin. Results Auranofin showed bactericidal activity at concentrations as low as 4.07 µg/mL, effectively reducing bacterial cell density by 50-70% and the viable vegetative cell and spore yields by 100%. The activity of auranofin was shown to be non-inferior to that of metronidazole and vancomycin. Conclusions Auranofin is highly efficacious against C. difficile M7404 in vitro and has the potential to be an ideal therapeutic option for the treatment of C. difficile infection.